2021
DOI: 10.1093/plphys/kiab242
|View full text |Cite
|
Sign up to set email alerts
|

DIOXYGENASE FOR AUXIN OXIDATION 1 catalyzes the oxidation of IAA amino acid conjugates

Abstract: Together with auxin transport, auxin metabolism is a key determinant of auxin signalling output by plant cells. Enzymatic machinery involved in auxin metabolism is subject to regulation based on numerous inputs, including the concentration of auxin itself. Therefore, experiments characterizing altered auxin availability and subsequent changes in auxin metabolism could elucidate the function and regulatory role of individual elements in the auxin metabolic machinery. Here, we studied auxin metabolism in auxin-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 49 publications
2
35
0
Order By: Relevance
“…At a high level of IAA in gh3-sept mutants, the group III GH3 enzymes, such as AtGH3.15 might produce IAA-amino acid conjugates to compensate for an impaired IAA inactivation in gh3-sept mutants, thereby accumulating small amounts of oxIAA. Recent work on IAA metabolite analysis indicated that oxIAA-Asp did not accumulate in DAO1 knockout tobacco BY-2 cultured cells and Arabidopsis dao1-1 mutants, suggesting that DAO1 oxidizes IAA-Asp in planta 28 .…”
Section: Discussionmentioning
confidence: 99%
“…At a high level of IAA in gh3-sept mutants, the group III GH3 enzymes, such as AtGH3.15 might produce IAA-amino acid conjugates to compensate for an impaired IAA inactivation in gh3-sept mutants, thereby accumulating small amounts of oxIAA. Recent work on IAA metabolite analysis indicated that oxIAA-Asp did not accumulate in DAO1 knockout tobacco BY-2 cultured cells and Arabidopsis dao1-1 mutants, suggesting that DAO1 oxidizes IAA-Asp in planta 28 .…”
Section: Discussionmentioning
confidence: 99%
“…DAOs and GH3s have been suggested to establish parallel and redundant pathways for IAA inactivation, with the GH3 pathway playing a compensatory function, as supported by increased and decreased conjugate concentrations in the DAO1 mutant and overexpressing plants, respectively (Porco et al ., 2016; Zhang et al ., 2016). This model has recently been challenged by the finding that IAA‐Asp is an in vivo substrate for the DAO1 oxidase, which additionally accounts for the formation of oxIAA‐Asp conjugates (Müller et al ., 2021). In a context where DAOs function downstream of group II GH3s, the reduced concentrations of oxIAA and oxIAA‐glc in gh3oct plants found in the present work suggest that a significant fraction of the plant oxIAA pool derives from oxIAA‐aa conjugates.…”
Section: Discussionmentioning
confidence: 99%
“…Several IAA‐Asp metabolites, including 6‐OH‐IAA‐Asp and oxIAA‐Asp, have been identified in the last few decades (Ostin et al ., 1998; Kai et al ., 2007). Recently, the IAA oxidase DAO1 was found to additionally operate in the GH3 pathway by mediating the formation of oxIAA‐Asp from IAA‐Asp in tobacco and Arabidopsis (Müller et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, It has also been proposed that Trp‐independent pathways are major contributors of auxin biosynthesis in maize and Arabidopsis but not in other non‐vascular plants (Normanly et al 1993; Wright et al 1991). Apart from biosynthesis, bioactive auxin levels in the cell are also determined through conjugation and oxidation (Mellor et al 2016; Müller et al 2021; Porco et al 2016). IAA conjugates to sugar through an ester bond, while it is bound to amino acids and peptides through amide‐linkage (Ludwig‐Müller 2011; Woodward & Bartel 2005).…”
Section: Introductionmentioning
confidence: 99%